Influence of workplace stress and social support on humanistic caring ability in Chinese nurses - Faqin Dong; Weiping Huang; Chunfei Chu; Lu Lv; Min Zhang (Wiley, 2023)
Abstract Aim This study aimed to examine the relationships between how workplace stress and social support affect the level of humanistic caring ability in Chinese nurses. Design A cross‐sectional study. Methods The sample consists of 675 nurses working in major hospitals in China. Participants completed a set of self‐reported measures, including the humanistic caring ability scale (HCAS), the Chinese nurse workplace stressor scale (CNWSS), the Chinese nurse stress response scale (CNSRS), and the Chinese nurse social support scale (CNSSS). Pearson's correlation analysis and structural equation modelling (SEM) were performed to investigate the relationships among studied variables. Results The result showed that HCAS was negatively correlated with CNWSS (r = −0.427, p < 0.01) and CNSRS (r = −0.480, p < 0.01), and was positively correlated with CNSSS (r = 0.363, p < 0.01). Furthermore, a final model was conducted in which CNWSS has a strong direct effect on CNSRS (β = 0.54, p < 0.01) and an indirect effect on HCAS (β = −0.138, p < 0.01), which was mediated by CNSRS and CNSSS.